1992
DOI: 10.1007/bf00008200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and species distribution in Coringa mangrove forest, Godavari Delta, Andhra Pradesh, India

Abstract: Coringa mangrove forest is located in the Godavari delta, Andhra Pradesh, India. The mangrove community consisted of more than 13 species of mangrove and other plants in the present study area. The following three dominant mangrove plants, Avicennia marina, Excoecaria agallocha and Sonneratia apetala were found to be present on the banks of a major channel of the Godavari river running through the forest. The structure and species distribution of mangrove, in the Channel Nagathana Kalava has been described. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…One way to characterize mangrove ecosystem, and to monitor changes is through the assessment of forest structure (10,11), these aspects being closely linked to forest productivity (12). Some of the structural parameters used are: tree height, stem diameter, basal area, crown diameter and leaf area index (11,13), from which other attributes like stand tables, regeneration rates, distribution patterns and complexity index can be derived. Structural studies have been used to describe the mangroves of Puerto Rico (14), and mangrove stands in Florida, Mexico and Costa Rica (15) among others.…”
Section: Introductionmentioning
confidence: 99%
“…One way to characterize mangrove ecosystem, and to monitor changes is through the assessment of forest structure (10,11), these aspects being closely linked to forest productivity (12). Some of the structural parameters used are: tree height, stem diameter, basal area, crown diameter and leaf area index (11,13), from which other attributes like stand tables, regeneration rates, distribution patterns and complexity index can be derived. Structural studies have been used to describe the mangroves of Puerto Rico (14), and mangrove stands in Florida, Mexico and Costa Rica (15) among others.…”
Section: Introductionmentioning
confidence: 99%
“…The rarely found species are Rhizophora apiculata, Xylocarpus moluccensis, Bruguiera cylindrica, Ceriops decandra and Bruguiera gymnorrhiza. Suaeda maritima and Suaeda nudiflora are found in hypersaline clayey mud soil (Azariah et al 1992;Ravishankar et al 2004b) …”
Section: Site 2 -Coringa Wildlife Sanctuarymentioning
confidence: 98%
“…Region-wise diversity of mangrove species, which include both true and associated species in India, is given in Mandal and Naskar (2008). A total of 13 species was reported from mangrove forests of Godavari region (Azariah et al, 1992). Azriah et al (1992) also reported a gradient in species diversity, with inland mangroves being highly diverse.…”
Section: % Mortalitymentioning
confidence: 99%
“…Studies in Indian mangroves have been along the lines of documenting biodiversity (Gopal and Chauhan, 2006), biomass (Mitra et al, 2011), nutrient dynamics (Kumar et al, 2011) and other conservation aspects, such as review of status (Jagtap et al, 1993;Gopal and Chouhan, 2006). Biodiversity studies in mangrove forests have focused on describing different species of both true mangrove and associates of mangrove formations in Sundarbans (Joshi and Ghose, 2003;Gopal and Chouhan, 2006), Godavari delta (Azariah et al, 1992), Bidarkarnika (Upadhyay and Mishra, 2008) or Andamans (Singh et al, 1987). There are hardly any studies on the quantitative aspects of vegetation diversity and growth rates on mangrove species, based on repeated stem measurements.…”
Section: Introductionmentioning
confidence: 99%